Analysing the Mathematical Critical and Creative Thinking Abilities in Problem Solving Introverted Students - Rahayu, Nurwanti Adi; Aoyama, Kazuhiro (Prodi Tadris Matematika Fakultas Tadris Umum, 2024)
This study aims to evaluate the critical and creative thinking abilities in the context of mathematics when solving problems related to arithmetic sequences and series among introverted students in the 11th grade at Xaverius 1 High School in Jambi City. This issue arises due to differences in thinking skills and cognitive processes among students based on personality types, where it was found that introverted students tend to have low mathematical critical and creative thinking abilities. The research method employed is a descriptive qualitative approach, collecting data through personality questionnaires, tests, and interviews. Research subjects were selected from introverted students based on personality questionnaire results and answer sheet analysis, with three students representing the various response groups. The results of this study indicate that introverted students demonstrate good mathematical critical thinking skills in understanding problems, planning, and implementing plans. However, they tend to overlook rechecking their solutions. The creative mathematical thinking abilities of introverted students mainly involve fluency and flexibility in understanding problems, planning, and implementing plans, although they lack in terms of originality and elaboration in problem-solving